Time-related manifestation of and perceptions on male sexuality among male prostitutes in Iloilo City. - Maquiling, Japril Anne T.; Severo, Ann Thea T. (2003.)
This descriptive study aimed to determined the significant difference in the manifestations of male sexuality among male prostitutes in Iloilo City during work shifts and days off, and to find out the male prostitutes perceptions on the stereotypes about male sexuality. The respondents of the study were twenty (20) male prostitutes in Iloilo City aging from 15 to 25. The researchers used snowball sampling in selecting the respondents. Time-related manifestations were measured using a5-point checklist type Likert scale and perception were measured using the Stereotypes About Male Sexuality Scale (SAMSS) by Dr. William E. Snell, Jr. The hypothesis of the study was: There is no significant difference in the manifestations of the male sexuality among male prostitutes during work shifts and days off (Ucomp= 127crit=127, p<0.05).
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Prostitutes, Male